Preservation of Regional Language and Culture on Nomadic Communities In Denpasar City, Bali - Susianti, Hartanti Woro; Asri, Anindhiasti Ayu Kusuma; Salindri, Anistya Ori (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2025)
Language and regional culture are essential in maintaining community identity, especially for nomadic groups residing in urban areas such as Denpasar, Bali. Increasing migration has intensified cultural interactions between newcomers and locals, creating threats to the sustainability of regional languages due to globalization and assimilation. This study explores strategies, challenges, and factors influencing language and cultural preservation among migrant communities in Denpasar using a qualitative case study approach. Data were obtained through in-depth interviews, participant observation, and archival documentation, and analyzed through reduction, presentation, and conclusion drawing. The findings show that preservation efforts include the use of regional languages within families, community-based cultural activities, and digital platforms such as social media. Key challenges involve globalization, pressure from Balinese cultural assimilation, and social stigma discouraging younger generations from practicing regional languages. Nevertheless, community initiatives, technological engagement, and supportive local government policies promoting cultural diversity serve as significant enablers. Overall, sustaining regional languages and cultures in Denpasar’s multicultural setting is crucial for safeguarding the identity and cultural heritage of migrant communities. egional languages. However, community support, technological engagement, and local government policies promoting cultural diversity have been key enablers of successful preservation efforts. Thus, sustaining regional languages and cultures in Denpasar’s multicultural context is essential to safeguarding the identity and cultural heritage of migrant communities.